Sebastian Black - local warming - Black, Sebastian 1985- (Zolo Press, 2021)
For Sebastian Black, 2020 was a year like no other: a pandemic; three exhibitions; a move to Los Angeles; a presidential election; a baby, too. Local Warming is Black's tale of it all, as recorded in his diary. "One million years ago, when I started making the paintings compiled here, I was listening to lots of audiobooks and recorded philosophy lectures. It was the winter of 2019, my paintings were about this and about that, and every brushstroke drifted safely over a net of ideas. I was gathering a list of things that I knew to be true because I was sick of having nothing to say when people asked me to explain myself. Then a professor, who to me is now a holy exegete, said that difference precedes identity as the substance of reality. I'd been eavesdropping on YouTube as he taught a continuing-ed class on Deleuze for a claque of narrative therapists. Difference before identity. I couldn't grasp the idea- only touch it. That's okay, said the professor, as though speaking directly to me, the point of thinking isn't to grasp things that are true but rather to prod things that are interesting.One interesting thing that happened recently was the birth of my son. He'd been the baby that was coming, a generalization, and then, in a moment that was so interesting it was almost terrible, he was himself. That was the beginning of the world, a specificity so sublime I thought I might go blind. A friend asked me what viewing the birth was like, and all I could say was that though I still didn't believe in god, I could understand why some people did because I'd seen him" ...
Limited run of 500 copies
Keywords: Black, Sebastian -- 1985-; Malerei; Thermografie; Black, Sebastian / 1985-; Painting, American; 2000-2099; Bildband